Matemática e linguagem: um estudo sobre leitura e escrita na sala de aula. - Luna, Amanda Silva Alencar (2011)
Researches in mathematics education have shown us, in recent years, the importance of the habit of reading in the classroom. The reading and textual production have been developing as a task to be undertaken in different areas of knowledge, especially in the discipline of mathematics. In order to analyze the practice of reading and writing in mathematics classes in early grades of elementary school, we conducted a bibliographic study, situated in the references on the subject, in order to elaborate the instruments used in research to survey data and to define the criteria for analysis. The main authors who were adopted in our benchmark are Vygotsky, Smola and Diniz, Silva, Lourenço and Côgo. Our research is a qualitative study, ethnographic type, and the elements used as the basis for our reflections were a result of observations by the action of the teacher in the classroom, the interview, to identify the conceptions of mathematics teacher in towards reading / writing classes in the discipline, and the analysis of the textbook adopted by him. Objective of this work is not to present as a result a proposal of action for use in the classroom by teachers, with a view of solving problems present today in our schools, but to provide support for teachers in training or already active professional to conduct reflections on the issues raised here and, based on their experience, alter their practices, seeking to improve the process of development of mathematical content in the classroom.